SPLIT ASSIGNMENT WITH TRANSPORTATION MODEL FOR JOB-SHOP LOADING (CASE STUDY) (Journal of Engineering, 2009)
The aim of this paper, is to analyze the assignment problem in industry where the constraint of allowing to allocate only one job to each machine is relaxed. Thus, splitting the job is permitted and processed by more than one machine. The problem is demonstrated with a real life case study. We solved the problem by splitting the jobs and converting lot of jobs as well as the actual hours of each machine to Standard Machine Hours (SMH). Transportation model is also suggested to overcome the problem, and the optimum solution is obtained by using POM software